2022
DOI: 10.1039/d1ra09073a
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of the coordination nanostructures of 4,4′,4′′-(1,3,5-triazine-2,4,6-triyl) tribenzoic acid molecules on HOPG triggered by the change in the concentration of metal ions

Abstract: A Cu2+ ion maintains coordination with two COOH groups, while a Fe3+ ion changes from coordination with three to two COOH groups after increasing the concentration of Cu2+/Fe3+ ions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…24−26 Additionally, a study has shown that the coordination structures are effectively tuned by adjusting the concentration of metal ions. 27 However, it has been rarely reported on the modulation of the coordination configuration by altering the solvent and metal ion concentration, which results in structural transformation of the molecular assembly.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…24−26 Additionally, a study has shown that the coordination structures are effectively tuned by adjusting the concentration of metal ions. 27 However, it has been rarely reported on the modulation of the coordination configuration by altering the solvent and metal ion concentration, which results in structural transformation of the molecular assembly.…”
Section: ■ Introductionmentioning
confidence: 99%
“…By selective modification of any of these parameters, various structural transformations can be effectively induced. For example, Deng et al demonstrated the dependence of molecular self-assembly on the solvent and solution concentration. Wang et al investigated the formation of diverse coordination structures by tuning the temperature and the type of metal ions. ,, The studies indicate that the incorporation of metal ions can convert relatively weak intermolecular bonds into metal coordination bonds with subsequent formation of metal coordination structures. Additionally, a study has shown that the coordination structures are effectively tuned by adjusting the concentration of metal ions . However, it has been rarely reported on the modulation of the coordination configuration by altering the solvent and metal ion concentration, which results in structural transformation of the molecular assembly.…”
Section: Introductionmentioning
confidence: 99%